Dimensi Tarbiyah dalam QS. Al-Mujadilah Ayat 11: Membangun Keseimbangan Intelektual, Spiritual, dan Sosial dalam Pendidikan Islam - Pitra Gosha Patriasya; Cucu Surahman; Elan Sumarna (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the educational (tarbiyah) dimensions in the Qur’an based on Surah Al-Mujadilah verse 11, focusing on achieving balance between intellectual, spiritual, and social aspects within Islamic education. The verse emphasizes that Allah elevates the ranks of those who believe and possess knowledge, highlighting the harmonious relationship between faith, knowledge, and social ethics in the learning process. The purpose of this study is to uncover the tarbawi values contained in the verse as a conceptual foundation for developing a holistic Islamic education framework. This research employs a qualitative method using a library-based study with a tafsir tarbawi approach, drawing upon classical sources such as Ibn Kathir and Al-Qurthubi, as well as contemporary literature on Islamic education. The findings reveal that Surah Al-Mujadilah verse 11 underscores the importance of integrating intellectual intelligence, spiritual depth, and social sensitivity as the core of educational development. These insights imply that Islamic education should not only prioritize knowledge acquisition but also foster moral character and spirituality as essential elements of lifelong learning.